2017
DOI: 10.1519/jpt.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Weight Bearing Asymmetry Using the Nintendo Wii Fit Balance Board Are Not Reliable for Older Adults and Individuals With Stroke

Abstract: Background Clinicians and researchers have used bathroom scales, balance performance monitors with feedback, postural scale analysis, and force platforms to evaluate weight bearing asymmetry (WBA). Now video game consoles offer a novel alternative for assessing this construct. By using specialized software, the Nintendo Wii Fit balance board can provide reliable measurements of WBA in healthy, young adults. However, reliability of measurements obtained using only the factory settings to assess WBA in older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Nintendo Wii is a therapy method that allows self-study. [ 8 ] Burns et al[ 9 ] reported in a study with healthy adults that Nintendo Wii games were well tolerated by individuals aged 21 to 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…Nintendo Wii is a therapy method that allows self-study. [ 8 ] Burns et al[ 9 ] reported in a study with healthy adults that Nintendo Wii games were well tolerated by individuals aged 21 to 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…That said, the absolute reliability assessed by standard error of measurement (SEM) is as important to be considered. Indeed, in the case of repetitive assessments, SEM is a parameter that indicates the amount of random error [8] (i.e., a lower value indicates good reliability [2]). In addition, the use of the SEM provides several advantages over relative reliability, as an estimate of reliability that includes the units of measurement can determine the minimal difference between the first and second evaluation to ACCEPTED MANUSCRIPT -CLEAN COPY 3 be considered as a true change and not just due to a test-retest error [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, his adult participants ranged from 18 to 57 years, which may have affected his results as the validity of Wii Fit could be age dependent. Liuzzo et al reported that Wii Fit was moderately reliable for the elderly above 65 years (ICC 0.59), and for adults and elderly with stroke from 54 to 80 years (ICC 0.60) 25) . However, the only Wii Fit parameter that they measured was percentage of left and right weightbearing which is more indicative of static alignment, rather than postural sway.…”
Section: Introductionmentioning
confidence: 99%